A possible risk of environmental exposure to HEV in Ibadan, Oyo State, Nigeria (2020)
"Hepatitis E virus (HEV) infection is both a major public health concern and emerging global health concern, with a documented incidence of 20 million, 3.4 million clinical cases, 70,000 deaths, and 3,000 stillbirths. The aetiologic agent, HEV is a primarily enterally transmitted hepatotropic virus. Fecal samples were collected from three selected pig farms across Ibadan, South-west Nigeria. Randomly picked samples were pooled per unit pen and fecal suspensions prepared were subjected to HEV Antigen (Ag) enzyme-linked immunosorbent assay. Molecular probing was done by Reverse Transcription and nested polymerase reaction (RT-nPCR) and deep sequencing. Sequencing was done paired-end for 300 cycles using the HiSeq system. Overall farm prevalence of 66.7% (2/3) and prevalence at individual level of 13.2% (9/68) were recorded. All nine samples positive for the ELISA screen were negative when subjected to RT-nPCR assays. Further, on deep sequencing, no HEV genomic fragment was found in the sample using de-novo assembly. Findings suggest possibly inapparent HEV in the pigs studied or a yet to be identified protein with HEV-Ag cross-reactivity ability on ELISA, thus constituting a possible risk of exposure to HEV infection in the population. Consequently, we recommend prompt intervention to unravel the mystery and break the chain of transmission.